Pre-clinical Pharmacokinetic and Metabolomic Analyses of Isorhapontigenin, a Dietary Resveratrol Derivative - Dai, Yu; Yeo, Samuel C. M.; Barnes, Peter J.; Donnelly, Louise E.; Loo, Lai C.; Lin, Hai-Shu (Frontiers in Pharmacology, 2018)
Background: Isorhapontigenin (trans‐3,5,4′‐trihydroxy‐3′‐methoxystilbene, ISO), a dietary resveratrol (trans‐3,5,4′‐trihydroxystilbene) derivative, possesses various health-promoting activities. To further evaluate its medicinal potentials, the pharmacokinetic and metabolomic profiles of ISO were examined in Sprague-Dawley rats. Methods: The plasma pharmacokinetics and metabolomics were monitored by liquid chromatography–tandem mass spectrometry (LC–MS/MS) and gas chromatography–tandem mass spectrometry (GC–MS/MS), respectively. Results: Upon intravenous injection (90 µmol/kg), ISO exhibited a fairly rapid clearance (Cl) and short mean residence time (MRT). After a single oral administration (100 µmol/kg), ISO was rapidly absorbed and showed a long residence in the systemic circulation. Dose-escalation to 200 µmol/kg resulted in higher dose-normalized maximal plasma concentrations (Cmax/Dose), dose-normalized plasma exposures (AUC/Dose) and oral bioavailability (F). One-week repeated daily dosing of ISO did not alter its major oral pharmacokinetic parameters. Pharmacokinetic comparisons clearly indicated that ISO displayed pharmacokinetic profiles superior to resveratrol as its Cmax/Dose, AUC/Dose and F were ~ 2 to 3 folds greater than resveratrol. Metabolomic investigation revealed that one-week ISO administration significantly reduced plasma concentrations of arachidonic acid, cholesterol, fructose, allantoin and cadaverine but increased tryptamine levels, indicating its impact on metabolic pathways related to health-promoting effects. Conclusions: ISO displayed favorable pharmacokinetic profiles and may be a promising nutraceutical in view of its health-promoting properties.